Robust strategies in nuclear-targeted cancer therapy based on functional nanomaterials - Qin Xiaofei; Zhang Hanyi; Xing Xin; Wang Peng; Yan Jiaqi; Liu Daishun; Gong Qiuyu; Zhang Renshuai; Zhang Hongbo (ELSEVIER SCI LTD, 2022)
Nucleus, as the machinery for genome transcription, play prominent roles to support the fundamental cel-lular functions, the destruction of any of these specific parts would significantly modulate the cell function. Therefore, troumendous drug delivery systems with enhanced nucleus targeting ability have been studied for nucleus-related disease regulation. The purpose of this review is to sort out the fundamental nuclear tar-geting strategy, especially the active mechanism of various nuclear targeting ligands and their extensive applications based on cancer targeting therapy. Various nuclear targeting ligands are first introduced to understand their nuclear entry mechanism. Next, to overcome biological barriers and avoid the serum pro-tein absorption, diverse robust delivery strategies based on different nuclear targeting ligands are dis-cussed. Moreover, other sophisticated carrier systems with enhanced nuclear entry, while without nuclear targeting ligands are also assembled. At the end the challenges and future opportunities in the field of nuclear targeting nanotherapeutics are tentatively proposed, to speed up their clinical translation. (c) 2022 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http:// creativecommons.org/licenses/by/4.0/).